Delays in diagnosing pulmonary tuberculosis within a context of medium incidence, Medellín, Colombia, 2017: an operational research - Iader Rodríguez-Márquez; Fernando Montes; Luz D. Upegui; Nilton Montoya; Nelly E. Vargas; Abelardo Rojas; Gloria C. Valencia; Claudia M. Álvarez; Leonardo Uribe; Jesús Ochoa (BMC, 2020)
Abstract Background Delay in tuberculosis (TB) diagnosis is one of the first obstacles for controlling the disease. Delays generate greater deterioration of the health of the patients and increase the possibilities of transmission and infection at home and in the community. The aim of the study was to identify profiles and individual variables associated with patient delays and health care system delays in patients with pulmonary tuberculosis (PTB) in Medellín, Colombia, a city that notifies 1400 new cases per year. Methods A retrospective cohort study in adults with PTB was conducted from May to September of 2017. Sociodemographic, health care-seeking behaviour, and clinical variables were measured. The outcomes were patient delay and health care system delay. The data were obtained from records of the local TB program, and a questionnaire was applied by the health care team that performs routine field visits. Simple correspondence analysis was used to identify groups (profiles), and their characteristics. Cox's proportional hazards model was carried out to identify the variables associated with the delays. Results The study included 183 patients. The total delay median was 101 days (IQR: 64-163). Patient delay was of 35 days (IQR: 14-84), the profile with greater delay belonged to consumers of psychoactive substances. The health care system delay was of 27 days (IQR: 7-89), the attributes of the profile with greater delay were being a female, having more than two consultations before the diagnosis, and having prescribed antibiotics. Basic-medium educational level [HRa = 0.69; 95% CI (0.49-0.97)] and having a TB home contact [HRa = 0.68; 95% CI (0.48-0.96)] were associated with greater patient delay. Having negative acid-fast bacilli (AFB) smear [HRa = 0.64; 95% CI (0.45-0.92)] and more than two consultations before the diagnosis [HRa = 0.33; 95% CI (0.22-0.49)] was associated with greater health care system delay. Conclusions Data from epidemiological surveillance allowed locating risk groups with delays in TB diagnosis which requires the prioritisation of the local TB control program to promote early detection and prevention of adverse outcomes.